Highly efficient electrical discharge machining of yttria-stabilized zirconia ceramics with graphene nanostructures as fillers. Issue 13 (October 2022) - Muñoz-Ferreiro, C.; López-Pernía, C.; Moriche, R.; Gommeringer, A.; Kern, F.; Poyato, R.; Gallardo-López, Á.
Abstract: Electrical-discharge machining (EDM) of advanced ceramics allows the miniaturization of parts with complex shapes. Since electrical conductivity is required, non-conductive ceramics need a conductive second phase. This work assesses the feasibility of industrial EDM in advanced yttria-stabilized tetragonal zirconia (3YTZP) composites with 20 vol% graphene nanostructures with different morphology using different EDM energies. The structural integrity of the graphene nanostructures, the roughness of the machined surfaces and the geometrical tolerances have been evaluated by Raman spectroscopy, confocal microscopy and scanning electron microscopy, showing that it is possible to obtain a stable and efficient EDM process in these composites using low electrode energies. The use of the largest and thickest graphene nanostructures led to the best performance in terms of EDM machinability, the smallest nanostructures produced the best surface finish for low electrode energy and the thinnest nanostructures allowed the highest material removal rate at medium energy in the composites. Graphical Abstract: ga1 Highlights: Conventional Electrical discharge machining success in graphene-zirconia composites. The process is stable at low-medium and high discharge energy for 20 vol% filler. Thicker graphene nanostructures allow machining at higher discharge energy. Surface roughness and tolerances are preserved after machining.